Heparin nanomodification improves biocompatibility and biomechanical stability of decellularized vascular scaffolds - Tao Y (Dove Medical Press, 2012)
Yunming Tao,1,2 Tiehui Hu,1 Zhongshi Wu,1 Hao Tang,1 Yerong Hu,1 Qi Tan,1 Chunlin Wu11Department of Thoracic and Cardiovascular Surgery, Second Xiangya Hospital of Central South University, Changsha; 2Department of Thoracic and Cardiovascular Surgery, Ji'an Central People’s Hospital, Ji'an, Jiangxi Province, People's Republic of ChinaAbstract: Biocompatibility and biomechanical stability are two of the main obstacles limiting the effectiveness of vascular scaffolds. To improve the biomechanical stability and biocompatibility of these scaffolds, we created a heparin-nanomodified acellular bovine jugular vein scaffold by alternating linkage of heparin and dihydroxy-iron via self-assembly. Features of the scaffold were evaluated in vitro and in vivo. Heparin was firmly linked to and formed nanoscale coatings around the fibers of the scaffold, and the amount of heparin linked was about 808 ± 86 µg/cm2 (101 ± 11 USP/cm2) per assembly cycle. The scaffolds showed significantly strengthened biomechanical stability with sustained release of heparin for several weeks in vitro. Importantly, the modified scaffolds showed significantly reduced platelet adhesion, stimulated proliferation of endothelial cells in vitro, and reduced calcification in a subcutaneous implantation rat model in vivo. Heparin nanomodification improves the biocompatibility and biomechanical stability of vascular scaffolds.Keywords: scaffolds, nanomodification, heparin, sustained release, biomechanical stability, biocompatibility